« HIV/aids awajun»: Notions and experiences of disease and sorcery in the context of an epidemic in the Peruvian Amazon - Flores Rojas, María Ximena (2020)
According to the memories of some Awajun families, since 2002 rumors about a new disease called «Aids», began to appear in the El Cenepa district. This apách, or non-indigenous condition, was incorporated into Awajun daily life as part of their experiences with illness (jata) and sorcery (waweamu), generating the notions of «jata Aids» and «waweamu with Aids symptoms». Far from a biomedical or epidemiological approach, this article presents other possible dimensions of thinking about HIV/aids in indigenous contexts. From the complexity of Awajun knowledge about their bodies and the forces that affect them. This article aims to understand the notions and experiences of illness and sorcery that the Awajun population have regarding HIV/aids.